Review of Fast Solar Jets and Coronal Mass Ejections - Sima Zeighami; Ehsan Tavabi (Iranian Journal of Astronomy and Astrophysics)
The Sun is a magnetically active star. It has a powerful magnetic field that shifts slightly from year to year until it reverses about every eleven years. The sun's magnetic field has many effects, the collection of which is called solar activity such as, sunspots, solar flares, and coronal mass ejections(CMEs). Currently, it is only possible to predict a magnetic storm 30 to 60 minutes before it occurs, which is a very short time. Solar flares and CMEs, massive eruptions of superheated plasma, are the two most energetic phenomenon which impulsively ejected and accelerated by releasing magnetic energy in the solar corona. Heliosphere, space weather, and the Earth are affected from transporting coronal plasma. Following the occurrence of these phenomenon in the Sun, the solar wind blows with greater speed and intensity and sends energetic charged particles into the space of the solar system. When these particles reach the Earth, their radiating electromagnetic waves interact with magnetic field of the Earth. Then various effects are observed, as shock waves and massive geomagnetic storms that disrupt satellites and power grids. Today, using the advancements of ground and space technology, the solar surface can be easily observed. Therefore, observation and prediction of solar storm will be possible more than in the past. In this paper, we review papers intended to collect comprehensive information about what has already been researched about fast solar jets and CMEs made by ground and space instruments over the last decades.